Steam based post-process pasteurization of beef salami for control of Listeria monocytogenes - V.S. Gill; H. Thippareddi; Randall K. Phebus; James L. Marsden; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2002)
We evaluated the destruction of Listeria monocytogenes on surfaces of artificially inoculated, vacuum-packaged beef salami by steam pasteurization (Stork RMA-Protecon Post-process Pasteurizer). Beef salami was inoculated with L. monocytogenes (initial concentrations of 4.36 log10 CFU/cm2 at the end and 4.49 at the middle), then pasteurized at 185, 194, or 203°F for 2 or 4 min. Only about 0.11 log10 CFU/cm2 (detection limit) L. monocytogenes survived after pasteurization at 203°F for 2 and 4 min, for a "kill rate" of over 99.99%. Post-packaging pasteurization reduces the threat of L. monocytogenes on the surfaces of cooked meat products.
Keywords: Cattlemen' s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Post-processing pasteurization; Beef salami; Listeria monocytogenes